Current Imaging Techniques for Lymph Node Staging in Prostate Cancer: A Review - Muteganya, Raoul; Goldman, Serge; Aoun, Fouad; Roumeguère, Thierry; Albisinni, Simone (Frontiers in Surgery, 2018)
ABSTRACT Introduction: Lymph node metastases (LNM) represent a proven prognostic factor for biochemical recurrence (BCR)-free survival, metastatic free survival and overall survival in prostate cancer (PCa). Although pelvic node dissection remains the gold standard for the detection of LNM, novel imaging techniques are entering clinical practice, in the effort to improve LNM detection and spare unnecessary surgeries. Aim of the current review is to describe such imaging techniques and explore their advantages and limitations. Evidence Acquisition: The National Library of Medicine Database was searched for relevant articles published between January 2013 and August 2018. A wide search was performed including the combination of following words: “Prostate” AND “Cancer” AND “staging” AND “Lymph Node” AND “imaging” AND ("MRI" OR "PET"). The initial list of selected papers was enriched by individual suggestions of the authors of the present review. Evidence synthesis: DWI-MRI in detection of lymph node invasion has a sensitivity and specificity of 41% and 94% respectively. For SPIO MRI using ferumoxtran-10, the sensitivity for detection of LNM with short axis diameter of 5-10 mm is reported at 96.4%, compared to 28.5% with MRI alone. PSMA PET/CT is growing exponentially, both in the initial detection of LNM and for BCR evaluation. Fluciclovine PET could improve detection of subcentimetric pathologic lymph nodes. Sentinel lymph node techniques remain experimental and not validated in the field of PCa. Conclusions Molecular imaging, particularly PSMA ligand PET imaging, present interesting diagnostic accuracy in LN diagnosis even in subcentimetric LN. DWI-MRI yields good results in LN involvement evaluation and the use of contrast agent such SPIO may improve the detection rate. The SLN technique is limited to experimental protocols and for intermediate or high-risk PCa. Prospective trials are awaited to evaluate the true clinical impact of these imaging techniques on PCa oncologic outcomes.